SYNTHESES OF CATION EXCHANGER WITH MACROPOROSITY AND INVESTIGATING SPECIFIC PROPERTIES - Shokhakimova Aziza Alimdjanovna; Turabdzhanov Sadritdin Maxamatdinovich; Kedelbayev Bakhitjan Shilmirzaevich; Peter Lieberzeit; Turaeva Dildora Sharifovna; Ponamaryova Tatyana Vladimirovna; Rakhimova Latofat Sobirjonovna (Academic Scientific Journal of Chemistry, 2020)
Obtained new strongly acid cation exchanger of macroporous structure based on furfural and dipheniloxide. The optimal amount of the poreformed agent and the molar ratio of the reacting substances were determined. Initially results showed that the polymer matrix using camphor as pore forming agent present a uniform surface with inter-connected pores and adding camphor into the polymer matrix could attain more abundant pores than adding n-heptane. We studied the components, surface and pore structures of the сation exchanger by Fourier transform infrared spectroscopy and scanning electron microscopy (SEM). SEM observations showed that the resin abounded in macropores as large as 7.4 to 22.6 µm both in the surface and the interior. The parameters of the porous structure of the samples are calculated using by equation BET (Brauner., at al.) and the total pore volume of ion exchangers and the radius of submicroscopic capillaries were determined. Finally dates testing prototypes under application conditions, allow us to recommend this cation exchanger for sorption of small radius ions at high speed, as fundamentals upon receipt of ion exchangers, etc.